Efektivitas Modul Ajar Berdiferensiasi Berbasis Sad Kerti Loka Bali pada Mata Pelajaran IPAS untuk Meningkatkan Kompetensi 4C Siswa - Putu, Agus Trisna (Universitas Galuh, 2026)
This study aims to examine the effectiveness of a differentiated instructional module based on Sad Kerthi Loka Bali in the Science and Social Studies (IPAS) subject for enhancing 4C Competencies (Critical Thinking, Creativity, Collaboration, Communication) among fifth-grade students in Cluster II, Busungbiu District during the 2024/2025 academic year. Employing a quantitative post-test-only control group design, data were collected through observations, interviews, and 4C competency questionnaires. The research population comprised all fifth-grade students (N=69) in Cluster II elementary schools, with a sample of 35 students divided between SD Negeri 1 Kedis (experimental group) and SD Negeri 3 Kekeran (control group). Data analysis commenced with normality and homogeneity tests, followed by t-test analysis (significance level α<0.05) of post-test results to determine the module's effectiveness in integrating Sad Kerthi Loka Bali values. The findings demonstrate that the differentiated instructional module significantly improved students' 4C competencies (Sig. [2-tailed] = 0.000 < 0.05). These results indicate that the locally-grounded Sad Kerthi Loka Bali-based IPAS module effectively enhances 4C competencies among fifth-grade students in Busungbiu District's Cluster II elementary schoolsThis study aims to examine the effectiveness of a differentiated instructional module based on Sad Kerthi Loka Bali in the Science and Social Studies (IPAS) subject for enhancing 4C Competencies (Critical Thinking, Creativity, Collaboration, Communication) among fifth-grade students in Cluster II, Busungbiu District during the 2024/2025 academic year. Employing a quantitative post-test-only control group design, data were collected through observations, interviews, and 4C competency questionnaires. The research population comprised all fifth-grade students (N=69) in Cluster II elementary schools, with a sample of 35 students divided between SD Negeri 1 Kedis (experimental group) and SD Negeri 3 Kekeran (control group). Data analysis commenced with normality and homogeneity tests, followed by t-test analysis (significance level α<0.05) of post-test results to determine the module's effectivene